Acute aortic dissection during minimally invasive cardiac surgery: a case report - Taisuke Kumamoto (JA Clinical Reports)
Abstract Background Management of acute aortic dissection (AAD) caused by retrograde perfusion through the femoral artery during minimally invasive cardiac surgery (MICS) remains controversial. We present a case of AAD occurring during the late cardiopulmonary bypass (CPB) phase, which was successfully managed by vascular graft replacement, without altering the blood supply route. Case presentation A 63-year-old man was scheduled for totally endoscopic aortic valve replacement. CPB was initiated through the right femoral artery and venous cannulation. Approximately 120 min after the initiation of CPB, mean arterial pressure and bilateral cerebral regional oxygen saturation temporarily decreased. Transesophageal echocardiography revealed type A AAD. Cerebral perfusion was preserved, allowing us to proceed to deep hypothermic circulatory arrest and successfully perform ascending aortic replacement without altering the blood supply route. Conclusions In MICS, continuous monitoring is crucial as AAD can occur at any point during CPB, and early detection enables successful outcomes.